Pengaruh Latihan Dynamic Stretching Dan Depth Jump Terhadap Peningkatan Vertical Jump Pada Pemain Bola Voli Di Smpn 1 Kauman Ponorogo - Meisatama, Herta, Totok Budi Santoso , S.Fis , MPH, Dwi Kurniawati, SST.FT, M.Kes (2015)
Background: a volleyball player must skilled to do vertical jump well, because it has some benefits and supports when the athletic performed defending/blocking and opponent smash. Leg's muscles power have an important role to create jumping, so, it could performs jumping smash and blocking perfectly (Cahyadinata, 2011). Objectives: to find about influence of dynamic stretching and depth jump giving to the vertical jump improvement of volleyball players in SMP N 1 Kauman. Research Method: method used in this research is quasi experiment. Research design is pre and posttest two groups design with comparing between vertical jump before and after the players performed dynamic stretching and depth jump. Results: Wilcoxon test results taken from dynamic stretching and depth jump is that, score of Sig p < 0.05 so, there is an influence of dynamic stretching and depth jump to the vertical jump. In Mann-Whitney Test score of Sig p < 0.05 so, there is the influence difference between dynamic stretching and depth jump. Conclusion: there is an influence in dynamic stretching and depth jump giving to improve the vertical jump. There is a difference of influence amount between dynamic stretching and depth jump to vertical jump improvement. Keywords: dynamic stretching, depth jump, and vertical jump